2014
DOI: 10.4274/turkderm.48902
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia syndrome in chronic urticaria patients

Abstract: Background and Design:The aim of our study was to determine the frequency of fibromyalgia syndrome in chronic urticaria patients. Materials and Methods: The study was carried out with the participation of 100 chronic urticaria patients and 61 control group patients. Chronic urticaria patients were investigated for the etiology of urticaria and the autologous serum skin test was performed in those patients. Both the chronic urticaria patients and the controls were evaluated for fibromyalgia syndrome, and the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In the current study, the FMS incidence in CSU patients (26.4%) was significantly higher than in the control group (8.2%). Similar studies comparing FMS prevalence in patients with chronic urticaria and healthy volunteers have shown that the FMS incidence in the urticaria group varied between 9.7% and 70.6% (15)(16)(17)(18)(19)(20). In all these studies, a higher FMS prevalence was observed in the urticaria group than in the control group, and, similar to our study, the difference in FMS prevalence between these two groups was statistically significant (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the current study, the FMS incidence in CSU patients (26.4%) was significantly higher than in the control group (8.2%). Similar studies comparing FMS prevalence in patients with chronic urticaria and healthy volunteers have shown that the FMS incidence in the urticaria group varied between 9.7% and 70.6% (15)(16)(17)(18)(19)(20). In all these studies, a higher FMS prevalence was observed in the urticaria group than in the control group, and, similar to our study, the difference in FMS prevalence between these two groups was statistically significant (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 86%
“…Similar studies comparing FMS prevalence in patients with chronic urticaria and healthy volunteers have shown that the FMS incidence in the urticaria group varied between 9.7% and 70.6% (15)(16)(17)(18)(19)(20). In all these studies, a higher FMS prevalence was observed in the urticaria group than in the control group, and, similar to our study, the difference in FMS prevalence between these two groups was statistically significant (15)(16)(17)(18)(19). Torresani et al compared 126 patients with chronic urticaria with 50 controls and used ACR 1990 criteria for diagnosing FMS.…”
Section: Discussionmentioning
confidence: 86%
“…12 Some studies have investigated FMS incidence in dermatologic disorders such as psoriasis 13 and chronic urticaria. 14 The FMS syndrome is known to cause functional disability and have a negative impact on patient's quality of life (QoL). 15 Moreover, depression and/or anxiety are important parameters in criteria for diagnosis of FMS.…”
mentioning
confidence: 99%